Media Anatomy-Based Literacy Terintegrasi Multimodal Counseling sebagai Penguatan Kompetensi Guru dan Kepribadian Produktif di Pendowo Kudus - Mahardika, Nur; Masfuah, Siti; Adiyono, Soni; Fakhriyah, Fina (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The Anatomy-Based Literacy Media Integrated Multimodal Counseling Program was designed in response to the lack of inclusive learning media for blind students in Pendowo Kudus, which results in low conceptual understanding and learning motivation as well as limited competence of guidance and counseling teachers in multisensorial technology. The community service methodology includes the development of tactile media such as 3D anatomical models, Braille books, and audio narratives teacher training in the use of inclusive media and multimodal counseling techniques, implementation in guidance sessions, and evaluation using quantitative (literacy tests, teacher competency surveys) and qualitative (interviews, observations of student personality) methods. The evaluation results show important achievements: understanding of anatomical concepts by blind students increased significantly through exploration of 3D tactile models, consistent with the finding that “blind students’ tactile perception is significantly more developed” and improves learning performance compared to conventional visual methods; teachers’ competence increased significantly in designing and using inclusive media and implementing multisensorial counseling effectively; and students’ productive personality aspects, such as self-confidence, independence, and creativity, developed positively. This confirms the effectiveness of the multimodal approach in strengthening teacher competency and facilitating the formation of productive personalities of blind students; thus, this program is recommended as an effective inclusive guidance and counseling service model to be replicated in other inclusive schools.